Pro windows phone app development - Software, Falafel (Apress Imprint: Apress, 2013)
The Windows Phone 8 platform provides a remarkable opportunity for Windows developers to create state-of-the-art mobile applications using their existing skills and a familiar toolset. Pro Windows Phone App Development, Third Edition, helps you unlock the potential of this platform and create dazzling, visually rich, and highly functional applications for the Windows Phone Store and bring you up to speed on the new features the Windows Phone 8 API provides. For developers new to the Windows Phone platform-whether with .NET, iOS, or Android experience-this book starts by introducing the requirements, specifications, and basics of Windows Phone development, and then leads you through the complete application development process, using an array of complementary technologies and Microsoft's modern-style app design. Along the way, you'll learn how to Use Microsoft technologies like XAML, .NET, Visual Studio 2012, and Expression Blend effectively to develop modern-style Windows Phone apps Take advantage of the device's sensors with the location service, accelerometer, and touch Make your apps location-aware using GPS data Develop rich media applications that harness the graphics capabilities of Windows Phone models Design and develop Windows Phone applications using the Model-View-ViewModel architecture Publish and sell your application through the Windows Phone Store Whether you're a Microsoft developer, an iOS or Android developer, or someone with prior Windows Phone experience, Pro Windows Phone App Development, Third Edition, is an ideal guide for mastering the Windows Phone 8 platform and compelling Windows Phone app development.